The association between Chlamydia pneumoniae infection and prognosis in lung cancer patients: a prospective study - Maolin Liu; Hailing Ye; Tao Lin; Zishan Chen; Xinying Xu; Jinman Zhuang; Yongsheng Yang; Xuezhen Chen; Chunting Chen; Mengxin Lin; Fei He (BMC Infectious Diseases)
Abstract Background The prognostic value of Chlamydia pneumoniae (Cpn) infection in postoperative lung cancer patients remains unclear. This study aimed to evaluate the association between Cpn infection and survival in lung cancer patients. Methods This study included 309 newly diagnosed primary lung cancer patients from three hospitals in Fuzhou, China. Chlamydia pneumoniae IgG and IgA antibodies were detected using a micro-immunofluorescence kit and a unified questionnaire was used to collect demographic and clinical information. Follow-up was conducted every six months until August 25, 2022, or death. Patients were followed up for a median duration of 74 months. Overall survival was compared between Cpn IgA and IgG positive/negative patients. Statistical analysis included the χ2 test, Kaplan-Meier method, Log-rank test, and Cox proportional hazards regression model. Results Cpn IgA infection status was found to be associated with lymph node metastasis in lung cancer patients. The overall survival of patients with Cpn IgA(++) was shorter compared to negative and positive patients(with IgA(-) group as the control group, P < 0.001, HR = 5.441, 95%CI: 2.341–12.645). Serum IgA positivity indicated chronic infection and was associated with poor prognosis. Multivariate analysis confirmed that Cpn IgA(++) infection was an independent risk prognostic factor for operable lung cancer patients (with IgA(-) group as the control group, HR = 3.39, 95%CI: 1.41–8.17). Conclusion This study suggests that Cpn infection is an independent prognostic factor in lung cancer patients. Further research is needed to understand the underlying mechanisms and explore the potential of Cpn as a biomarker or therapeutic target for lung cancer.